The Contribution to Missiology by United Methodist Scholarship on Evangelism - Teasdale, Mark R. (Missiology, 2013)
United Methodist scholars have contributed significantly to the emerging critical study of evangelism. In doing so, they have also contributed to the study of mission. This is because the Methodist approach to the study of evangelism allows for a broad set of definitions for evangelism, multiple methodologies for considering evangelism, and a wide array of activities that can fall under the rubric of evangelism. This essay demonstrates the breadth of this contribution by reviewing texts authored by United Methodist scholars of evangelism from the 1970s to the present.